Infrastructure and Poverty: State Budget Effect Analysis with Panel Model - Nurul Azizah Az Zakiyyah (Universitas Ahmad Dahlan, Yogyakarta, 2023)
The problem of poverty has an impact on various socio-economic problems such as high levels of illiteracy and unemployment, low levels of health and a bad environment. One strategy to reduce poverty can be done by building adequate infrastructure. The quality of advanced infrastructure is the main prerequisite needed by a country to accelerate its economic growth and development. This study focuses on the effect of infrastructure development that uses economic growth as a